Unpacking Formation Mechanisms of Social Innovation Initiatives in Cuernavaca, Mexico - Lüken, Harmke Jan; Zapf, Jan (Malmö University, 2021)
This study seeks to unpack the formation mechanisms of social innovation (SI) initiatives in Cuernavaca, Mexico. Subsequently, this study employs a qualitative case study to investigate (1) local embedding, (2) trans-local connectivity and (3) university linkages of SI initiatives in Cuernavaca. Previous research indicated that socio-spatial dynamics are critical for the development of SI initiatives. Furthermore, previous research asserted that universities are imperative to SI in the context of Latin America. Nevertheless, previous research contemplating the formation mechanisms of SI was primarily westerncentric and displayed an inadequacy to acknowledge SI in the context of Latin America. Based on previous research this study presents a theoretical framework that classifies the results in eight typologies based on (1) local embedding, (2) trans-local connectivity and (3) university linkages. All three dimension are classified as either "high" or "low", which grants insights into influential formation mechanisms. Subsequently, a sample of n=10 SI initiatives was compiled and twelve semi-structured interviews with representatives of the SI initiatives were conducted. The results indicate three typologies of SI initiatives. Five SI initiatives were classified as: HLH – high local embedding, low trans-local connectivity, and high university linkages. Four initiatives were classified as: LHH – low local embedding, high trans-local connectivity, and high university linkages. One initiative was classified as HLL – high local embedding, low trans-local connectivity, low university linkages. The results indicate that SI initiatives either seek to address local challenges or direct their efforts to trans-local challenges. Furthermore, universities evidently play a critical role in the formation of SI initiatives in Cuernavaca and Mexico. This study contributes to SI literature by presenting evidence that universities possess critical roles in the formation of SI. Future research should increasingly embed universities into theoretical approaches when investigating SI formation mechanism in Latin America.
Keywords: Amérique latine; Libre accès